Case Study: A Japanese patient with metastatic renal cell carcinoma who achieved long‐term treatment‐free survival with pembrolizumab and axitinib in the KEYNOTE‐426 phase III trial of pembrolizumab and axitinib versus sunitinib. Issue 3 (18th February 2022) - Nishimoto, Koshiro; Shirotake, Suguru; Miyama, Yu; Kaneko, Go; Kanao, Kent; Igarashi, Daisuke; Takahashi, Takayuki; Umezawa, Yuta; Yasuda, Masanori; Oyama, Masafumi
Abstract : Introduction: Our patient treated with pembrolizumab and axitinib is one of the longest survivors in Japan on KEYNOTE 426, despite adverse events, including delayed‐onset hepatitis. We herein present a detailed clinical course and short discussion on the case. Case presentation: This was a 49‐year‐old male with clear cell renal cell carcinoma and lung metastases. After cytoreductive nephrectomy, treatment with pembrolizumab plus axitinib was initiated and the patient demonstrated a radiographic partial response as best response. The main adverse event was pembrolizumab‐induced delayed‐onset hepatitis, which was successfully treated with prednisolone. Pembrolizumab was re‐initiated and completed. Conclusion: The survival benefit in the present case may be due to the initial potent anti‐cancer effects of axitinib and durable immune effects of pembrolizumab, leading to long‐term treatment‐free survival.